(untitled) (The Pretoria Student Law Review, 2025)
In theory, the right to democratic participation in Africa is safeguarded by an array of international and regional human rights instruments, such as article 13 of the African Charter on Human and Peoples’ Rights. In essence, the right entails the genuine freedom of people to participate in government and to vote freely, without coercion, intimidation, or deception. In recent times, there has been a growing concern about the impact of artificial intelligence (AI) on the enjoyment of human rights. Deepfake, a relatively new concept, is one of such AI-controversy. Recently, scholars have considered the impacts of deepfakes on different areas of law, such as intellectual property, torts and evidence. In human rights discourse, discussions on deepfake have focused particularly on the right to dignity and privacy. But in fact, the right to information is probably the human right most endangered by deepfake. This article seeks to underscore that there is a concerning impact on the right to democratic participation. First, the article shows the interdependence and interrelation between the right to democratic participation and the right information. Thereafter, it argues that the right to information makes sense only when seen as ‘the right to truth’. Further, it argues that deepfake interferes with the ‘freely’ component of the right to democratic participation in that it disturbs and distorts information necessary for the electorates to freely participate in government. The article notes the little response from African states despite the call from the African Commission to establish a framework for human rights in the use of AI and emphasises the importance of partnership with technology companies in addressing the problem. Other recommendations made include the need to educate the electorates on deepfakes and the formulation of law and policy compatible with the African Charter in addressing the problem.